2011
DOI: 10.1093/molbev/msr276
|View full text |Cite
|
Sign up to set email alerts
|

Evidence for Horizontal Gene Transfer from Bacteroidetes Bacteria to Dinoflagellate Minicircles

Abstract: Dinoflagellate protists harbor a characteristic peridinin-containing plastid that evolved from a red or haptophyte alga. In contrast to typical plastids that have ∼100-200 kb circular genomes, the dinoflagellate plastid genome is composed of minicircles that each encode 0-5 genes. It is commonly assumed that dinoflagellate minicircles are derived from a standard plastid genome through drastic reduction and fragmentation. However, we demonstrate that the ycf16 and ycf24 genes (encoded on the Ceratium AF490364 m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
27
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 27 publications
(28 citation statements)
references
References 38 publications
1
27
0
Order By: Relevance
“…There are a small number of genes that are not found in other plastid lineages and are specific to individual peridinin dinoflagellate species (29,30). It has additionally been suggested that the plastids of the peridinin dinoflagellates Ceratium horridum and Pyrocystis lunula may contain a small number of genes acquired through lateral transfers from bacterial sources although it cannot be excluded that these genes have been misidentified from bacterial contamination in the original sequence datasets (31). Many of the genes that have been lost uniquely from the peridinin plastid genome are known to have relocated to the nucleus and have acquired targeting sequences allowing the import of the expression products into the plastid (28,32).…”
Section: Dinoflagellates In the Context Of Plastid Integrationmentioning
confidence: 99%
“…There are a small number of genes that are not found in other plastid lineages and are specific to individual peridinin dinoflagellate species (29,30). It has additionally been suggested that the plastids of the peridinin dinoflagellates Ceratium horridum and Pyrocystis lunula may contain a small number of genes acquired through lateral transfers from bacterial sources although it cannot be excluded that these genes have been misidentified from bacterial contamination in the original sequence datasets (31). Many of the genes that have been lost uniquely from the peridinin plastid genome are known to have relocated to the nucleus and have acquired targeting sequences allowing the import of the expression products into the plastid (28,32).…”
Section: Dinoflagellates In the Context Of Plastid Integrationmentioning
confidence: 99%
“…The best known is the ribosomal protein rpl36 gene, which was transferred from a proteobacterium or a planctomycete bacterium to plastid genomes of cryptophytes and haptophytes [180]. The other examples are genes encoding the large and small subunits of RuBisCO form I, acquired by the primary plastid genome of the common ancestor of red algae from a proteobacterium [152] (for additional cases, see [181,182] and references therein).…”
Section: Reasons Behind Inconsistencies In Inferring Relationships Bementioning
confidence: 99%
“…Brembu et al have found traces of horizontal gene transfer in the chloroplast genome of the diatom Seminavis robusta [29]. Moszczynski et al have shown that the genome of Dinoflagellate Minicircles has genes that are closely related to those in Algoriphagus and/or Cytophaga bacteria belonging to the Bacteroidetes clade [30], suggesting the transfer of these genes to have occurred relatively recently. Some horizontally transferred genes confer key functions on algae to better survive in changing environments; for instance, diatom genes encoding enzymes in the ornithine-urea cycle (considered to have been transferred from bacteria) facilitate their metabolic response to episodic nitrogen availability [31 ].…”
Section: Introductionmentioning
confidence: 99%